Assessment of outdoor lighting installations and their impact on light pollution using unmanned aircraft systems - The concept of the drone-gonio-photometer. (September 2020) - Bouroussis, Constantinos A.; Topalis, Frangiskos V.
Highlights: A new proposed method for the measurement and assessment of the obtrusive light and the light pollution. Introduction of the concept of the Drone-Gonio-PhotoMeter (DGPM) Proposed lighting measurement geometries for aerial platforms Assessment of lighting installations fast and easily from the air Presentation of preliminary test cases. Abstract: This paper presents the ongoing research of the lighting laboratory to develop a standardized method for the measurement of several types of lighting installations using unmanned aircraft systems. The technology of unmanned aircraft systems can incorporate multiple types of sensors and can be programmed to fly in predefined areas and routes in order to perform complex measurements with limited human intervention. This technology provides the freedom of measurements from several angular positions and altitudes in a fast, easy, accurate and repeatable way. The overall aim of this work is to assess the lighting installations, not only against the applicable lighting standards but also to investigate and reveal issues related to light pollution and obtrusive lighting. The latter are issues that in most cases are neglected due to the lack of standardized methods of calculation and measurement. Current assessment methods require illuminance or luminance measurements of horizontal and vertical surfaces generally from the ground. The proposed approach provides a holistic three-dimensional evaluation of the lighting installations beyond the common methods and geometries and opens the discussion for future update of the relevant standards on outdoor lighting. In the scope of this paper, several proof-of-concept cases are presented.